Benin English Teachers' Awareness of the Developmental Values of Classroom Observations - TEBA, Corneille Sourou; HOUMASSÈ, Roger; Hounhanou, Arlette Joséline Viviane (My University, 2018)
This paper examines the level of awareness of Benin English teachers regarding the importance of classroom observations in their professional growth. It should be placed in the general context of what are being done to gear the English language teaching in Benin towards successful and effective oral and written communication. It also aims at developing critical thinking ability in each teacher. The degree of Benin English teachers’ involvement in their personal development through classroom observations was gauged through a questionnaire. One hundred and eighteen teachers were randomly selected to participate in the survey. The investigation revealed that teachers do not have common practice of classroom observation. They have judgmental and punitive views on it. To restore the place of classroom observations in the process of Benin teachers’ professional growth, the study showed their beneficial aspects and also suggested some strategies for their full integration into in-service teachers’ habits.
Keywords: Classroom Observation; Self Observation; Peer Observation & Teacher Development